Pemberdayaan Petani Melalui Penyuluhan dan Pembuatan Pupuk Organik untuk Meningkatkan Sektor Pertanian serta Mendukung Pertanian Berkelanjutan di Kismantoro, Kabupaten Wonogiri - Purwanta; Qardhawi Ikhsan; Abdul Malik Siddiq; Afina Putri Widyasari; Ari Susanti; Eka Wahyuni Anamika; Moh. Rizky Alamsyah; Nurjanati Uzlifah; Priyanita Wingga Ermala; Raisma Nadhifa; Rezangtika Alfawwazi Turhadi (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Kismantoro, Wonogiri Regency, Central Java is an area with a tropical climate and is situated in highlands, primarily dominated by agricultural land. Additionally, the cattle farming sector, particularly for cows and goats is extensively developed in Lemahbang and Pucung Villages, which are located on the border between Central Java and East Java. The potential of agricultural and livestock products in both villages is quite large, making agriculture and livestock one of the leading sectors. In order to optimise the management of agriculture and livestock, a work program was conducted with counselling and making of organic fertiliser. The basic ingredients are easy to obtain, low cost, and easy to make can be a potential economic value for farmers and breeders. The purpose of this program is to optimise the production of organic fertiliser to improve the development of the agricultural sector and support sustainable agriculture in Kismantoro. The method used in this activity is data collection in three ways, observation, interviews, and recording. Sampling was carried out using a purposive sampling method and data analysis techniques were carried out with qualitative descriptions. In this program, counselling, and technical guidance on making Jakabawhich is aliquid fertilizer that can aid in the growth and development of plants, made from rice water, household waste-based liquid oraganic fertilizer, and solid organic fertiliser based on livestock manure was held. The products from this program are two plasticcontainers of organic fertilisers that are ready to be applied to soil and plants. The knowledge provided in this program can also be applied and practised independently or collectively by the community so that it can optimise the agricultural sector of Kismantoro and support sustainable agriculture. Thus, this program can indirectly improve the welfare of the community, especially in Kismantoro.